2015
DOI: 10.5664/jcsm.5288
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Sleep Technologies: A Review of the Landscape

Abstract: Objective: To review sleep related consumer technologies, including mobile electronic device "apps," wearable devices, and other technologies. Validation and methodological transparency, the effect on clinical sleep medicine, and various social, legal, and ethical issues are discussed. C onsumer sleep technologies (CSTs) are increasingly popular computer-based systems available to the general public for the purpose of improving or self-monitoring sleep. Their primary goals include sleep induction, wake inducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
148
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 189 publications
(155 citation statements)
references
References 19 publications
0
148
0
2
Order By: Relevance
“…Self‐management applications have been used in CLBP, which could be used as outcomes or to attain intervention adherence . For example, fitness applications (with or without the use of a smartwatch) could be used to track daily physical activity and exercise progressions, weight loss, diet and nutrition, mood, and sleep quality . The utility of such applications could be used to quantify day‐to‐day or week‐to‐week results of various outcomes, rather than being solely collected at periods where individuals report back to their healthcare provider .…”
Section: Multidimensional Assessment Of Chronic Low Back Painmentioning
confidence: 99%
“…Self‐management applications have been used in CLBP, which could be used as outcomes or to attain intervention adherence . For example, fitness applications (with or without the use of a smartwatch) could be used to track daily physical activity and exercise progressions, weight loss, diet and nutrition, mood, and sleep quality . The utility of such applications could be used to quantify day‐to‐day or week‐to‐week results of various outcomes, rather than being solely collected at periods where individuals report back to their healthcare provider .…”
Section: Multidimensional Assessment Of Chronic Low Back Painmentioning
confidence: 99%
“…In the current era of wearable technology, the impact of digitally delivered feedback on behaviour, cognition and health is of clinical and scientific importance (Patel, Asch, & Volpp, 2015;Piwek, Ellis, Andrews, & Joinson, 2016). In relation to sleep, there is mounting concern that so-called "sleep tracking" devices have limited evidence of validity or reliability (Behar, Roebuck, Domingos, Gederi, & Clifford, 2013;Ko et al, 2015;Lee & Finkelstein, 2014;Van den Bulck, 2015). For example, one recent study found that a leading commercial device markedly underestimated total sleep time and sleep efficiency relative to polysomnography in patients with major depression (Cook, Prairie, & Plante, 2017).…”
mentioning
confidence: 99%
“…Moreover, consumer sleep technologies now are transforming the way populations consider their sleep health. 25 The field of sleep medicine can debate the pros and cons of this emerging phenomenon and its collective effect on sleep, but this paradigm shift affords an opportunity to consider how the practice of sleep medicine may evolve in coming years. In particular, it is important to contemplate how these changes may increase the efficiency of sleep providers, improve access to sleep services, and reduce the cost of providing sleep care.…”
Section: Em Br Aci Ng the Ro Le O F Co Nsum Er Sleep Techno Log I Esmentioning
confidence: 99%